Ghana : Selected Issues Paper. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper discusses growth strategy for Ghana. Ghana has achieved impressive development gains over the last decades, with rising incomes, lower poverty, and better health, education, and gender outcomes. However, growth has recently become less inclusive, with high inequality and slower poverty reduction. In order to address these challenges, the authorities are pursuing a 'Ghana beyond Aid' development strategy centered around agricultural modernization and export-led industrialization. Accelerating productivity growth calls for fostering competition, improving the business environment, strengthening human capital, taking advantage of growing regional markets and industrial policies that prioritize sectors that can export and innovate and where Ghana could achieve economies of scale. Consistent and predictable government policies can help increase long-term investment and improve public spending effectiveness. A key lesson from growth accelerations in other countries is that it is crucial to achieve economies of scale. In most cases, rapid economic growth required achieving export success in specific sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet